A comparative study of paperless partograph and modified WHO partograph in management of labour - Verma, Krupa; Monika; Panwar, Babita; Hooja, Nupur; Gurjar, Kapil Kumar; Saini, Aakanksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Maternal mortality ratio (MMR) in India has declined to 97 deaths per lakh in 2020. Though the use of partograph for monitoring of women in labour helped in the decline, several factors have been implicated in the underuse and incorrect use of the modified WHO partograph at all levels of maternity care. A paperless partograph has been designed for use by clinicians in low resource areas as a simple, non-time consuming, two step calculation to monitor progress of labour, the time to intervene or to transfer a woman to higher centres with facilities for caesarean section. Aim of the study was to compare paperless partograph and modified WHO partograph in the management of labour. Methods: 1040 women who were admitted in labour room were selected and divided into two equal. Group A women were assessed during labour using modified WHO partograph and Group B women using paperless partograph. Outcome was observed were: Spontaneous normal delivery or assisted normal delivery or caesarean section, duration of labour, no. of women delivering before or at ALERT ETD, between ALERT and ACTION ETD and others delivering beyond ACTION ETD, indication for caesarean section if done. Foetal outcome was also recorded: APGAR scores, NICU admissions (reason of admission, duration of stay, outcome and compared. Results: There was no significant difference in mode of delivery between both the partographs (p-value= 0.771488). The outcome in terms of time taken from 4 cm to to delivery and delivery in relation to Alert and Action line / ETD was comparable. Conclusions: Paperless partograph can be easily used in place of modified WHO partograph in low resource settings with similar outcome.